(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the problems of educational quality that arise in the process of introducing digital technologies in the modern education system. Digital technologies play a significant role in making education more interactive and effective. However, there are some obstacles to their introduction into the education system, including providing teachers with digital competence, insufficient technological infrastructure, and problems of effective integration. The article considers ways to solve these problems.